2015
DOI: 10.3174/ajnr.a4237
|View full text |Cite
|
Sign up to set email alerts
|

Dilated Perivascular Spaces in the Basal Ganglia Are a Biomarker of Small-Vessel Disease in a Very Elderly Population with Dementia

Abstract: BACKGROUND AND PURPOSE: Dilated perivascular spaces have been shown to be a specific biomarker of cerebral small-vessel disease in young patients with dementia. Our aim was to examine the discriminative power of dilated cerebral perivascular spaces as biomarkers of small-vessel disease in a very elderly population of patients with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 18 publications
7
53
1
1
Order By: Relevance
“…A higher global PVS score was correlated with a greater burden of WMH in lobar regions and the basal ganglia, which supports the view that PVS, along with WMH, are markers for cerebral small-vessel disease. 9,19,33 More interesting, we found a correlation between the PVS score in the basal ganglia and WMH load not only in the same region but also in lobar areas, while we did not find any correlation between the lobar PVS score and WMH load either in the lobar areas or in the basal ganglia. This is in line with the view that PVS, especially in the basal ganglia, are caused mainly by hypertensive arteriopathy, like WMH, while lobar PVS are mainly due to cerebral amyloid angiopathy or amyloid accumulation in the brain with normal aging.…”
Section: Discussioncontrasting
confidence: 39%
“…A higher global PVS score was correlated with a greater burden of WMH in lobar regions and the basal ganglia, which supports the view that PVS, along with WMH, are markers for cerebral small-vessel disease. 9,19,33 More interesting, we found a correlation between the PVS score in the basal ganglia and WMH load not only in the same region but also in lobar areas, while we did not find any correlation between the lobar PVS score and WMH load either in the lobar areas or in the basal ganglia. This is in line with the view that PVS, especially in the basal ganglia, are caused mainly by hypertensive arteriopathy, like WMH, while lobar PVS are mainly due to cerebral amyloid angiopathy or amyloid accumulation in the brain with normal aging.…”
Section: Discussioncontrasting
confidence: 39%
“…In dementia, while dilated perivascular spaces around arteries are not common in the cerebral cortex, in the WM and basal ganglia dilated perivascular spaces are present and thought to indicate an impaired solute and ISF clearance (Roher, et al, 2003,Weller, et al, 2015). Dilated perivascular spaces have been suggested as a valuable biomarker of small vessel disease among the elderly population (Hansen, et al, 2015) and may be due to glymphatic dysfunction (Wostyn, et al, 2016). In our study, we observed dilated perivascular spaces around arteries in the striatum that significantly correlate to WM damage.…”
Section: Discussionmentioning
confidence: 99%
“…Two clinical studies showed that high grade BG EPVS were related to Alzheimer's disease and vascular dementia compared to NCA or frontotemporal dementia [26,27]. Previous recent studies also showed a role for BG EPVS in dementia and MCI.…”
Section: Discussionmentioning
confidence: 99%